Party System Volatility in Post-Communist Europe. Issue 1 (14th July 2016) - Crabtree, Charles; Golder, Matt
Abstract : In their 2014 article in the British Journal of Political Science, Eleanor Neff Powell and Joshua A. Tucker examine the determinants of party system volatility in post-communist Europe. Their central conclusion is that replacement volatility – volatility caused by new party entry and old party exit – is driven by long-term economic performance. This article shows that this conclusion is based entirely on a miscalculation of the long-term economic performance of a single country, Bosnia-Herzegovina. The study's reanalysis suggests that little is known about what causes party system volatility in post-communist Europe. Given the negative consequences traditionally associated with party system volatility, this area of research cries out for new theoretical development.